2022
DOI: 10.3233/rnn-211245
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of cerebellar tDCS and task-oriented circuit training in people with multiple sclerosis: A pilot randomized control trial

Abstract: Background: Balance and mobility impairments are frequent in people with multiple sclerosis, partly due to cerebellar dysfunctions. Task-oriented behavioural approaches were previously shown to promote physical function. The possibility exists that cerebellar transcranial direct current stimulation (ctDCS) applied during training, known to increase the excitability of the brain, can boost rehabilitation effects through modulation of cerebellum-brain inhibition. Objective: To test the efficacy of cerebellar ctD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Among the 17 included trial groups, two received rTMS ( 31 , 35 ), two used tRNS ( 25 , 30 ), one received remote tDCS ( 21 ), one applied iTBS ( 37 ) and the remaining 11 groups were all studied for the use of tDCS ( 22 24 , 26 29 , 32 34 , 36 ). In total, nine trials ( 21 , 23 , 26 29 , 33 , 34 , 36 ) set a single 20-min intervention, three trials ( 30 32 ) having a stimulus duration of 15 min for one intervention, and two trails ( 22 , 24 ) applied a single 30-min intervention; this parameter was not described in three additional studies ( 25 , 35 , 37 ). Regarding the cognitive function ( 21 , 25 30 ), all 10 investigations used a stimulus intensity of ≤2 mA, with a stimulation location in the left dorsolateral prefrontal cortex, except one study located over the right parietal cortex (P4) ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 17 included trial groups, two received rTMS ( 31 , 35 ), two used tRNS ( 25 , 30 ), one received remote tDCS ( 21 ), one applied iTBS ( 37 ) and the remaining 11 groups were all studied for the use of tDCS ( 22 24 , 26 29 , 32 34 , 36 ). In total, nine trials ( 21 , 23 , 26 29 , 33 , 34 , 36 ) set a single 20-min intervention, three trials ( 30 32 ) having a stimulus duration of 15 min for one intervention, and two trails ( 22 , 24 ) applied a single 30-min intervention; this parameter was not described in three additional studies ( 25 , 35 , 37 ). Regarding the cognitive function ( 21 , 25 30 ), all 10 investigations used a stimulus intensity of ≤2 mA, with a stimulation location in the left dorsolateral prefrontal cortex, except one study located over the right parietal cortex (P4) ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the evaluation of the quality of the included articles showed in Figures 2 , 3 , the randomization method was not reported in five of them ( 21 , 25 , 30 , 35 , 36 ), and the methods reported in the remaining articles included computer randomization, technician randomization, and randomization list. Five articles ( 26 , 29 , 32 34 ) reported its allocation and concealment; most of the studies included were double-blinded and apart from that, three studies ( 27 , 28 , 31 ) didn't reported its blind method, two articles ( 21 , 35 ) didn't use blind method, and two articles ( 24 , 30 ) used single blind method. Six studies ( 25 27 , 29 , 30 , 32 ) reported adverse effects, such as headache, nausea, itches, and insomnia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the research has proved that CPC closed-loop rehabilitation is more effective than single central or peripheral therapy in managing post-stroke dysfunctions, such as motor impairment, aphasia, and dysphagia, and treatment options include tDCS + FES, tDCS + electromyographic biofeedback, tDCS + TOT, rTMS + TOT, and so on (Wang et al, 2012;Baroni et al, 2022; Figure 3). This is reflected in both physiological indicators and clinical manifestations, including motor evoked potentials, the modified Ashworth scale, the Fugl-Meyer motor function assessment, the water drinking test, and so on (Shaheiwola et al, 2018;Muhle et al, 2021).…”
Section: Application Of Central-peripheral-central Closed-loop Rehabi...mentioning
confidence: 99%
“…The combination of NIBS and motor or behavioral intervention has gained substantial interest over the last years due to the promising potentiality that the combined approach offers [ 3 ]. Several studies on post-stroke patients combined NIBS and rehabilitative approaches such as intensive physiotherapy or occupational therapy [ 7 , 8 ], robot-assisted training [ 9 , 10 , 11 ], virtual reality rehabilitation [ 12 , 13 , 14 , 15 ], and task-oriented training [ 16 ] for promoting motor recovery. Between the available NIBS techniques, transcranial magnetic stimulation (TMS) has been used to investigate and induce plasticity in the human brain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%